Informasi Kinerja Pemerintah Daerah di Media Online - Nur Imroatus Sholikhah (Jurnal Media dan Komunikasi Indonesia, 2021)
Digital era is characterized by a rapid growing information, one of them is online media. Despite many criticisms regarding journalistic ethic and the value of its news, online media is still considered as a trustworthy information resources compared to other means which are unattached to journalistic ethic. The need of people towards information from online media, especially associated with public local information, one of them is the local government performance (Pemda). This study focuses on potential of online media as a reliable information resource of government accomplishment by identifying a consistent content about local government presenting in the news, how to connect one information to another and build public knowledge towards local government implementation. The method of study using quantitative analysis and data retrieval by machine extraction – Data Intelligence Media Management (IMA). The result demonstrates that there are two kinds of information presented by online media which are regional information performance and facts concerning government performance, through OPD information and government officials. Information on regional performance has greater exposure rather than information on government performance; tends to be dominated by crisis and performance information related to the interests of non-local governments. Meanwhile, government information tends to be dominated by the performance of regional heads compared to other local government officials. On the other side, the focus of OPD performance information tends to follow regional news trends. This trend is largely due to indicators of the dissemination of information on local government performance through information dissemination strategies.